KEBIJAKAN FORMULASI JUDI ONLINE DALAM HUKUM INDONESIA - Bunga, Dewi (Institut Hindu Dharma Negeri Denpasar, 2019)
Various electronic devices equipped with internet networks have opened up opportunities for emerging crimes in cyberspace. Online gambling is a form of traditional crime transformation that turns into a crime operating in cyberspace. In the formulation of legal policies in various countries, not all countries declare online gambling as a criminal act. There are countries that legalize online gambling, there are countries that are in the gray area, and some are banningonline gambling. In this study there are two issues discussed, namely the application of jurisdiction in the criminal acts of online gambling and criminal law policies against online gambling. The application of jurisdiction in criminal acts of online gambling must pay attention to the rules of international law, where a country cannot enforce its rule of law in another country. Provisions regarding online gambling jurisdiction are regulated in Article 2 of Act Number 11 of 2008concerning Electronic Information and Transactions. International cooperation in law enforcement on online gambling can be carried out as long as there are international agreements between countries and both countries alike establish online gambling as a crime. Criminal law policy on online gambling in Indonesia formulates online gambling as a criminal act as stipulated in Article 27 paragraph (2) of Act Number 11 of 2008 concerning Information and Electronic Transactions.